Actinic Cheilitis Prevalence and Risk Factors: A Cross-sectional, Multicentre Study in a Population Aged 45 Years and Over in North-west Spain - Isabel Rodríguez-Blanco; Ángeles Flórez; Carmen Paredes-Suárez; Romina Rodríguez-Lojo; Daniel González-Vilas; Aquilina Ramírez-Santos; Sabela Paradela; Ignacio Suárez Conde; Manuel Pereiro-Ferreirós (Medical Journals Sweden, 2018)
Actinic cheilitis is thought to be a premalignant lesion or a superficial squamous cell carcinoma. The prevalence of actinic cheilitis in Europe is unknown. The aim of this study was to determine the prevalence of actinic cheilitis in the Galicia region (north-west Spain). Secondary objectives were the description of risk factors of actinic cheilitis. A cross-sectional multicentre study in patients ≥ 45 years of age was performed in 8 dermatology departments in Galicia region during a 1-year period. The prevalence of actinic cheilitis was 31.3%. Significant and independent risk factors of actinic cheilitis after multivariate analysis were age ≥ 60 years, Fitzpatrick skin phototype II, outdoor working for more than 25 years, and previous history of non-melanoma skin cancer. This is the first cross-sectional multicentre study of the prevalence of actinic cheilitis in Europe. Actinic cheilitis was present in almost one-third of the screened patients. Lip examination should be performed in all patients with chronic actinic damage.